Accelerated aging in people experiencing homelessness: A rapid review of frailty prevalence and determinants - Mantell, Rhys; Hwang, Ye In Jane; Radford, Kylie; Perkovic, Silvija; Cullen, Patricia; Withall, Adrienne (Frontiers in Public Health, 2023)
Introduction: Older people experiencing homelessness (PEH) are a rapidly growing population at risk of accelerated ageing and the early onset of geriatric conditions. One construct that shows promise in predicting age-related decline is frailty. Better understanding the rates and causes of frailty in PEH may improve understanding of its antecedents, thereby facilitating more targeted health and aged care service interventions. The aim of this study was to conduct a rapid review on the prevalence and determinants of frailty in adult PEH. Methods: We conducted a rapid review of primary research papers studying PEH and frailty or frailty-related concepts. Results: 14 studies were included, which indicate that frailty presents earlier and at higher rates in PEH than community-dwelling cohorts. A notable difficulty for many ageing PEH was early-onset cognitive impairment which was associated with a range of negative functional outcomes. Another recurrent theme was the negative impact that drug and alcohol use and dependence can have on the health of PEH. Further, psychosocial and structural determinants such as loneliness, living in an impoverished neighbourhood and being female had statistically significant associations with frailty and functional decline in PEH. Discussion and Implications: PEH in their 40s and 50s can be frail and experience geriatric conditions, including cognitive impairment. Factors that have important relationships to frailty and functional decline in PEH include cognitive deficits, drug and alcohol dependence and loneliness, as well as upstream determinants such as gender and ethnicity. More targeted data and research on these factors, including cohort studies to better investigate their potentially causal effects, is important for researchers and practitioners assessing and treating frailty in PEH, particularly those interested in early intervention and prevention.